2013
DOI: 10.1039/c3ra44666b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [18F]4-(4-fluorophenyl)-1,2,4-triazole-3,5-dione: an agent for specific radiolabelling of tyrosine

Abstract: We developed a new [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Similarly, a three component Mannich reaction between tyrosine and imines formed from aldehydes and electron rich anilines has also been described (entry 7) (Joshi et al, 2004), although it is relatively slow and requires a large excess of regents (McFarland et al, 2008; Romanini and Francis, 2007). The aqueous ene-type reaction of tyrosine with cyclic diazodicarboxamides seems more generally promising (Ban et al, 2010; Ban et al, 2013; Jessica et al, 2013), which reacts selectively at the o-position of the phenol side chain, and was shown to be thermally and hydrolytically stable (entry 8).…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
“…Similarly, a three component Mannich reaction between tyrosine and imines formed from aldehydes and electron rich anilines has also been described (entry 7) (Joshi et al, 2004), although it is relatively slow and requires a large excess of regents (McFarland et al, 2008; Romanini and Francis, 2007). The aqueous ene-type reaction of tyrosine with cyclic diazodicarboxamides seems more generally promising (Ban et al, 2010; Ban et al, 2013; Jessica et al, 2013), which reacts selectively at the o-position of the phenol side chain, and was shown to be thermally and hydrolytically stable (entry 8).…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
“…The synthetic strategy involved the alkynylation of tyrosine units of the nontoxic mutant diphtheria toxin CRM197, a protein carrier in many licensed vaccines, via 1,2,4‐triazoline‐3,5‐dione (TAD) chemistry followed by the attachment of glucan chains via azide‐alkyne click chemistry. TAD functionalization was also recently used to radiolabel tyrosine of natural proteins using [18F]4‐(4‐fluorophenyl)‐1,2,4‐triazole‐3,5‐dione . In another example, Bauer et al prepared bifunctional TAD linkers and showed protein–DNA conjugation …”
Section: Introductionmentioning
confidence: 99%
“…TAD functionalization was also recently used to radiolabel tyrosine of natural proteins using [18F]4-(4-fluorophenyl)-1,2,4-triazole-3,5-dione. [25] In another example, Bauer et al prepared bifunctional TAD linkers and showed protein-DNA conjugation. [26] While TAD-mediated conjugation of tyrosine in natural proteins is feasible, the applicability of this chemistry in synthetic polymers was explored by Stadler and Kuhrau [27] and more recently by DuPrez and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, first attempts have been undertaken to introduce PTAD derivatives onto radiochemistry using either aliphatic tosylate precursor which gave poor results or by multi-step synthesis, starting with nucliophilic aromatic substitution of nitrobenzene compound with leaving group on para-position (Jessica et al, 2013). Here, we describe an innovative simple procedure by avoiding time consuming azeotropic drying to obtain a radiofluorinated PTAD using sulfonyl chloride precursor.…”
Section: Resultsmentioning
confidence: 98%